Existence of Serotonin and Neuropeptides-Immunoreactive Endocrine Cells in the Stomach (Proventriculus and Gizzard) of Long-Legged Buzzard (Buteo rufinus): An Immunohistochemical Study - Atalar, Omer; Bayrakdar, Ali (Medwell Online, 2011)
This study aimed to determine the existence and distribution of serotonin and certain neuropeptides in proventriculus and gizzard of the long-legged buzzard by using peroxidase anti-peroxidase complex immunohistochemical technique. In both proventriculus and gizzard, serotonin, Somatostatin-14 (SOM-14), Substance P (SP) and Calcitonin Gene Related Peptide (CORP)-IR endocrine cells were determined. However, Cholecystokinin-8 (CCK-8), neurotensin, Neuropeptide Y (NPY), galanin and Vasoactive Intestinal Polypeptide (VIP)-IR endocrine cells were not found in any region of the stomach. Serotonin-IR endocrine cells were detected in the epithelium and glands of both stomach regions however, they were more intense in the glands of gizzard. Numerous in number SOM-14-IR endocrine cells were detected in the glands of the stomach. A few SP-IR endocrine cells were detected in the epithelium of the whole stomach and in the glands of gizzard. Moderate CGRP-IR endocrine cells were detected only in the epithelium of whole stomach. In conclusion, serotonin, SOM-14, SP and CGRP were detected to exist in the proventriculus and gizzard of the long-legged buzzards for the first time in the present study. It was also found that this species has been found to differ from other types of some avian species.
Keywords: Serotonin; neuropeptides; endocrine cell; stomach; long-legged buzzard; immunohistochemistry